Sulfite Oxidation in Chlorobaculum Tepidum - Rodriguez, Jesse; Hiras, Jennifer; Hanson, Thomas E. (Frontiers in Microbiology, 2011)
The green sulfur bacterium Chlorobaculum tepidum is proposed to oxidize sulfide and elemental sulfur via sulfite as an obligate intermediate. The sulfite pool is predicted to be contained in the cytoplasm and be oxidized by the concerted action of AprBA, which directly oxidizes sulfite, and QmoABC, which transfers electrons from AprBA to the quinone pool. Like other green sulfur bacteria, C. tepidum was unable to use exogenously provided sulfite as the sole electron donor. However, exogenous sulfite significantly stimulated the growth yield of sulfide limited batch cultures. The growth of C. tepidum mutant strains, CT0867::TnOGm and CT0868::TnOGm, was not increased by sulfite. Furthermore, these strains accumulated sulfite and displayed a growth yield decrease when grown on sulfide as the sole electron donor. These results support an obligate, cytoplasmic sulfite intermediate as part of the canonical sulfur oxidation pathway in C. tepidum that requires the Qmo-complex for oxidation.